2022
DOI: 10.47102/annals-acadmedsg.2021308
|View full text |Cite
|
Sign up to set email alerts
|

The impact of deprescribing interventions on oral proton pump inhibitor utilisation in a Singapore tertiary hospital: A quality improvement initiative

Abstract: Introduction: Proton pump inhibitors (PPIs) are effective treatments for upper gastrointestinal pathologies and short-term courses are well-tolerated. However, indiscriminate use of PPIs is undesirable due to its potential harms. We implemented a series of deprescribing interventions between 2016 and 2017 to curb PPI overutilisation in our institution. The aim of this study was to evaluate the effectiveness and safety of these interventions. Methods: An institutional PPI deprescribing guide was disseminated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In studies using the PATD or rPATD questionnaires, there is mixed evidence on the associations between certain patients' characteristics and their willingness to have their medications deprescribed. For example, age and willingness to have medications deprescribed were found to be positively associated in four studies, 20,21,29,30 negatively associated in another four studies, 18,19,22,31 and non‐significant in 15 other studies 23–27,32–41 . Among the 21 studies that examined the association between patient willingness to have a medication deprescribed and the number of medications, three found a positive association, 20,22,23 one a negative association, 34 and 17 found no significant association 21,24–27,29,30,32,33,36,37,39,40,42–45 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In studies using the PATD or rPATD questionnaires, there is mixed evidence on the associations between certain patients' characteristics and their willingness to have their medications deprescribed. For example, age and willingness to have medications deprescribed were found to be positively associated in four studies, 20,21,29,30 negatively associated in another four studies, 18,19,22,31 and non‐significant in 15 other studies 23–27,32–41 . Among the 21 studies that examined the association between patient willingness to have a medication deprescribed and the number of medications, three found a positive association, 20,22,23 one a negative association, 34 and 17 found no significant association 21,24–27,29,30,32,33,36,37,39,40,42–45 .…”
Section: Introductionmentioning
confidence: 97%
“…For example, age and willingness to have medications deprescribed were found to be positively associated in four studies, 20,21,29,30 negatively associated in another four studies, 18,19,22,31 and non-significant in 15 other studies. [23][24][25][26][27][32][33][34][35][36][37][38][39][40][41] Among the 21 studies that examined the association between patient willingness to have a medication deprescribed and the number of medications, three found a positive association, 20,22,23 one a negative association, 34 and 17 found no significant association. 21,[24][25][26][27]29,30,32,33,36,37,39,40,[42][43][44][45] These unclear findings support the need for more research on what factors are associated with the patients' willingness to have their medications deprescribed.…”
mentioning
confidence: 99%
“…Most published data on PPI de‐prescribing relate to ambulatory or residential care settings 10,12,15 . To our knowledge, only one other study, by Calvo et al ., investigated PPI de‐prescribing during acute hospital admissions 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Most published data on PPI de-prescribing relate to ambulatory or residential care settings. 10,12,15 To our knowledge, only one other study, by Calvo et al, investigated PPI de-prescribing during acute hospital admissions. 9 This study showed a better de-prescription rate at 3 and 6 months, 75% and 72%, respectively, and a higher patient participation rate of 69%.…”
Section: Discussionmentioning
confidence: 99%